Romania : Staff Report for the 2010 Article IV Consultation, Fourth Review Under the Stand-By Arrangement, and Requests for Modification and Waiver of Nonobservance of Performance Criteria-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2010)
The growth outlook remains weak and uncertain. Romania's decision to rely primarily on expenditure cuts to close the fiscal gap is ambitious, but entails implementation risks. Progress on fiscal reforms has resumed. In the medium term, fiscal policy should aim at a more permanent reduction in the fiscal deficit. The government's proactive banking supervision, and regulation has helped maintain the stability of the financial system, but vigilance is essential. Pressing ahead with structural reforms is key for boosting growth and achieving sustainable real convergence.